2012
DOI: 10.4162/nrp.2012.6.5.414
|View full text |Cite
|
Sign up to set email alerts
|

Effect of coenzyme Q10 andArdisia japonicaBlume on plasma and liver lipids, platelet aggregation, and erythrocyte Na efflux channels in simvastatin-treated guinea pigs

Abstract: Forty guinea pigs were divided into four groups and fed 0.04% cholesterol based control diet, plus 0.05% simvastatin, and statin plus 0.1% CoQ10 or 10% Ardisia Japonica Blume (AJB) leave powder for 4 weeks. Plasma total cholesterol levels decreased significantly in all groups fed the statin-containing diet compared with that in guinea pigs fed the control diet (P < 0.01). Plasma and liver triglycerides decreased significantly in the statin plus CoQ10 group compared with those in the control (both P < 0.05). Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
(44 reference statements)
2
2
0
Order By: Relevance
“…Our study showed a significant decrease of cholesterol and triacylglycerol levels in the liver of animals treated with ATV and CoQ 10 , compared with those rats that only received ATV. These results are in coincidence with other reports [ 11 ] that suggest CoQ 10 improves the hypolipemiant action of statins. As we already mentioned it is not currently known the mechanism by which CoQ 10 increases statins action.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study showed a significant decrease of cholesterol and triacylglycerol levels in the liver of animals treated with ATV and CoQ 10 , compared with those rats that only received ATV. These results are in coincidence with other reports [ 11 ] that suggest CoQ 10 improves the hypolipemiant action of statins. As we already mentioned it is not currently known the mechanism by which CoQ 10 increases statins action.…”
Section: Discussionsupporting
confidence: 92%
“…These results support a better hypolipidemic effect of ATV in the presence of CoQ 10 . This improvement in the effect of ATV by CoQ 10 has already been reported in Guinea pigs [10,11]. …”
Section: Discussionsupporting
confidence: 77%
“…Treatment with CoQ10 revealed a significant decrease in serum cholesterol and TG when compared with the DOX group and a significant increase when compared with DOX/Gin group. The improvement in the hypolipidemic effect of atorvastatin by CoQ10 has already been reported in Guinea pigs [43].…”
Section: The Central Vein (C) At the Center Of Classic Hepatic Lobule And Cords Of Hepatocytes With Large Rounded Vesicular Nuclei (Arrowmentioning
confidence: 57%
“…Blume (A. japonica) was selected as the experimental plant. A. japonica, which belongs to the Myrsinaceae family, is widely distributed in South China (Kang et al, 2012). Since its first recording in an ancient Chinese encyclopedia called Compendium of Materia Medica (Bencao Gangmu), A. japonica has been used in China for thousands of years.…”
Section: Introductionmentioning
confidence: 99%